2020
DOI: 10.3390/v12060634
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lamivudine-Based Antiretroviral Treatment on Hepatitis B Viremia in HIV-Coinfected South Africans

Abstract: This prospective study investigated the impact of lamivudine-containing antiretroviral therapy (ART) on HIV-positive patients in South Africa with baseline hepatitis B virus (HBV) infection. Follow-up samples from 56 HBV/HIV co-infected patients, 25 with occult HBV infection (OBI) and 31 with chronic HBV infection (CHB), were available for analysis. HBV viral loads were quantified at 6, 12, 18, and 24 months post-ART initiation by the COBAS TaqMan HBV Test 48 assay, and the HBV polymerase gene was amplified wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…Regarding the choice of 3TC in simplified treatment schemes, its use has been proven to be ineffective in the control of HBV replication even in HIV HBcAb-positive patients treated with triple ART. A recent South African prospective study investigating the impact of 3TC-containing ART regimens on the trend of HBV viremia during 24 months of follow-up demonstrated that 25% of patients with proven OBI had detectable HBV DNA at 24 months after the introduction of 3TC [ 12 ]. In addition, the possibility of HBV-immune escape mutant emergence is a well-known phenomenon in patients treated with 3TC [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the choice of 3TC in simplified treatment schemes, its use has been proven to be ineffective in the control of HBV replication even in HIV HBcAb-positive patients treated with triple ART. A recent South African prospective study investigating the impact of 3TC-containing ART regimens on the trend of HBV viremia during 24 months of follow-up demonstrated that 25% of patients with proven OBI had detectable HBV DNA at 24 months after the introduction of 3TC [ 12 ]. In addition, the possibility of HBV-immune escape mutant emergence is a well-known phenomenon in patients treated with 3TC [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…In PLWH subjects with OBI, it has been shown that the initiation of ART containing lamivudine (3TC) or TDF achieves the durable suppression of HBV-DNA [ 8 ], and occasional cases of HBV reactivation in PLWH subjects with OBI have been reported after discontinuation of the anti-HBV drug [ 9 , 10 ]. Moreover, treatment of HIV/HBV-coinfected patients with 3TC in the ART composition, once widely carried out in resource-limited settings, is currently not recommended due to the rapid loss of drug efficacy owing to the emergence of resistant strains in most subjects [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rtV173L + rtL180M + rtM204V triple mutant combination, which was observed in two participants at enrolment and persisted at follow up in one participant, has been shown to cause amino acid changes in the overlapping surface gene, resulting in reduced anti-HB binding [9,39]. This triple mutant has been reported with higher frequency in patients infected with HBV genotype A, and who are also HIV co-infected [40]. This was notably evident in this study, where all sequences clustered around genotype A1 and were mostly HIV co-infected.…”
Section: Discussionmentioning
confidence: 96%
“…In cohort analyses from Cameroun, Malawi and South Africa, the use of LAM without TDF was linked to the gradual emergence of resistance mutations in the HBV polymerase gene. [25][26][27] The proportion of individuals with detectable HBV VL on LAM monotherapy who developed resistance reached 88% in an HIV cohort from The Gambia. 20 Given the significant proportion of participants who were on a sub-optimal ART regimen for HBV therapy and the studies on renal function trajectories in PLWH in SSA to date, individuals on TDF were three times more likely to develop moderate or severe renal dysfunction compared to those on other NRTI, but the incidence of severe renal dysfunction events was low.…”
Section: Discussionmentioning
confidence: 99%
“…These findings underline the high likelihood of resistance development during LAM HBV monotherapy, as shown in previous studies in the region. In cohort analyses from Cameroun, Malawi and South Africa, the use of LAM without TDF was linked to the gradual emergence of resistance mutations in the HBV polymerase gene 25–27 . The proportion of individuals with detectable HBV VL on LAM monotherapy who developed resistance reached 88% in an HIV cohort from The Gambia 20 .…”
Section: Discussionmentioning
confidence: 99%